Institutional Perspectives on Women’s Entrepreneurship in the UK Equity Funding Sector - Zheng, Chenyu (2021)
This research aims to understand the institutional embeddedness of women’s entrepreneurship in the UK equity financing sector. In specific, it seeks to explore institutional barriers faced by women entrepreneurs in the UK when securing equity funding and examine how the issue of under-representation of women in the UK equity financing sector has been tackled. Through a lens of institutional theory, nine detailed case studies were conducted over a three-month period to achieve research objectives. It has identified several institutional barriers in the industry from macro, meso, and motherhood levels. By advancing the understanding of the relationship between women in institutional practices and their strategic choices in a dynamic entrepreneurial environment, the issue of gender gap in the UK equity financing sector has been tackled exogenously and endogenously through institutional change and institutional work. Thus, the study contributes to our understanding about the role of women investors play in a specific institutional context, and also have an influence by advancing the acceptance of gender difference as a social construct.